Fluence Map Prediction Using Deep Learning Models – Direct Plan Generation for Pancreas Stereotactic Body Radiation Therapy - Wang, Wentao; Sheng, Yang; Wang, Chunhao; Zhang, Jiahan; Li, Xinyi; Palta, Manisha; Czito, Brian; Willett, Christopher G.; Wu, Qiuwen; Ge, Yaorong; Yin, Fang-Fang; Wu, Q. Jackie (Frontiers in Artificial Intelligence, 2020)
Purpose: Treatment planning for pancreas stereotactic body radiation therapy (SBRT) is a difficult and time-consuming task. In this study, we aim to develop a novel deep learning framework to generate clinical-quality plans by direct prediction of fluence maps from patient anatomy using convolutional neural networks (CNNs). Materials and Methods: Our proposed framework utilizes two CNNs to predict intensity modulated radiation therapy fluence maps and generate deliverable plans: 1) Field dose CNN predicts field dose distributions in the region-of-interest using planning images and structure contours; 2) Fluence map CNN predicts the final fluence map per beam using the predicted field dose projected onto the beam’s eye view. The predicted fluence maps were subsequently imported into the treatment planning system for leaf-sequencing and final dose calculation (model-predicted plans). One hundred patients previously treated with pancreas SBRT were included in this retrospective study, which were split into 85 training cases and 15 test cases. For each network, 10% of training data were randomly selected for model validation. Nine-beam benchmark plans with standardized target prescription and organ-at-risk constraints were planned by experienced clinical physicists and used as gold standard to train the model. Model-predicted plans were compared with benchmark plans in terms of dosimetric endpoints, fluence map deliverability, and total monitor units. Results: The average time for fluence map prediction per patient was 7.1 seconds. Comparing model-predicted plans with benchmark plans, target mean dose, maximum dose (0.1 cc), and D95% absolute differences in percentages of prescription were 0.1%, 3.9%, and 2.1%, respectively; organ-at-risk mean dose and maximum dose (0.1 cc) absolute differences were 0.2% and 4.4%, respectively. The predicted plans had comparable fluence map gamma index (97.69% ± 0.96% vs. 98.14% ± 0.74%) and total monitor units (2122 ± 281 vs. 2265 ± 373) to the benchmark plans. Conclusions: We developed a novel deep learning framework for pancreas SBRT planning, which predicts fluence map for each beam and can therefore bypass the lengthy inverse optimization process. The proposed framework could potentially change the paradigm of treatment planning by harnessing the power of deep learning to generate clinically deliverable plans in seconds.